An association between religiosity level and condom use behavior - Madni, Abdul Rehman; Abdul Hamid, Norsiah; Mohd Rashid, Sabrina (IISTE, 2016)
Condom has become inevitable need of all those who are involved in sexual relations. It is one of the best ways to protect from unintended or unwanted pregnancies, but in Muslims societies common people have a shock when they listen that condom use is prohibited in Islam or un-Islamic.Several Muslims express a desire to avoid pregnancy but do not use contraception because of religious concerns.Religious followers with high religiosity level strongly and strictly accept the religious doctrine and strictly follow all the principles, rules, code and ethics of their religion. Studies suggest investigating the association between religious factors and consumer behavior with religiosity by using more reliable and definitive measures and religiosity should be tested in a religious context, particularly if there are strictures against an object in one denomination and the inclusion of object for other denominations.